Optimalisasi Penggunaan Media Sosial Facebook dalam Meningkatkan Pemasaran UMKM Bawang Merah di Desa Ngasem - Mauhala Sofa; Adita Nafisa (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
Effective marketing is the key to success for shallot farmers in increasing sales and obtaining optimal profits. Social media, especially Facebook, can be an effective tool for promoting and marketing shallot products. This research aims to analyze the optimization of the use of Facebook social media in increasing shallot marketing in Ngasem Village. The use of social media Facebook can effectively increase shallot marketing in Ngasem Village. The optimization strategies carried out include creating a Facebook business page, managing interesting content, utilizing advertising features, as well as intensive interaction activities with customers. By implementing this strategy, shallot farmers and traders can increase product visibility, expand marketing reach, and encourage increased sales.